KEBIJAKAN DIVIDEN SEBAGAI PEMODERASI: STRUKTUR MODAL DAN NILAI PERUSAHAAN - Budiadnyani, Ni Putu; Dewi, Pande Putu R. Aprilyani; Prena, Gine Das (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
A firm's market value is a vital measure that encapsulates its overall operational performance and appeals to investors. Optimizing the capital structure can enable companies to bolster their value proposition and appeal to investors. This study investigates the relationship between capital structure and firm value, with the potential for dividend policy to act as a moderating factor. Comprehending the interplay between these elements is crucial in shaping the company's capital decisions and their subsequent impact on enhancing its market value. The research was conducted online through the official website of the Indonesia Stock Exchange, focusing on all Consumer Goods Companies listed on the IDX from 2020 to 2022. Purposive sampling was used to determine the study's sample. The analysis employed linear regression and moderate regression analysis methods with the assistance of SPSS for Windows statistical application. The findings suggest that capital structure does not affect firm value. Interestingly, this result implies that dividend policy may diminish the impact of capital structure on firm value. These insights underscore the significance of aligning funding strategies with appropriate dividend policies to maximize firm value and appeal to investors.